2022
DOI: 10.1109/access.2022.3193402
|View full text |Cite
|
Sign up to set email alerts
|

On the History and Future of 100% Renewable Energy Systems Research

Abstract: Research on 100% renewable energy systems is a relatively recent phenomenon. It was initiated in the mid-1970s, catalyzed by skyrocketing oil prices. Since the mid-2000s, it has quickly evolved into a prominent research field encompassing an expansive and growing number of research groups and organizations across the world. The main conclusion of most of these studies is that 100% renewables is feasible worldwide at low cost. Advanced concepts and methods now enable the field to chart realistic as well as cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(143 citation statements)
references
References 389 publications
(600 reference statements)
4
111
0
Order By: Relevance
“…Recent examples include Brown and Botterud (2021), Larson et al (2021), EPRI (2021) and DeAngelo (2021). There are also reviews and summaries of several studies provided by Azevado et al (2021), Bistline (2021), andBreyer et al (2022). Among the goals of this present study is to contribute to this larger body of work, much of which examines various pathways and timelines.…”
Section: Introductionmentioning
confidence: 91%
“…Recent examples include Brown and Botterud (2021), Larson et al (2021), EPRI (2021) and DeAngelo (2021). There are also reviews and summaries of several studies provided by Azevado et al (2021), Bistline (2021), andBreyer et al (2022). Among the goals of this present study is to contribute to this larger body of work, much of which examines various pathways and timelines.…”
Section: Introductionmentioning
confidence: 91%
“…Other geographic entities have not yet been reviewed in detail, except some overviews on selected global 100% RE systems analyses in general [10], [12], [66], [67], and sector-specific analyses for the transport sector [68], heat sector [69], and storage [70]. The most studied cities in the world are New York City [71], [72], [73], [74], [75], [76] and Aalborg in Denmark [77], [78], [79], [80] with six and four studies, respectively, but no further city in the world with more than two detailed studies could be identified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several possibilities to both reduce the GHG emissions from the energy-industry system and meet the growing global energy demand. Some options are energy efficiency, phasing out fossil fuels, and thus the promotion of RE [8], [9], finally leading to an entirely RE system [10]. 100% RE systems have been analyzed by a growing number of researchers to find solutions for a sustainable energy system [11] and understand a feasible approach to mitigate climate change impacts, air pollution, energy poverty, and the most cost-effective energy systems [10], [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…A new study led by Breyer [1] has synthesized much of the work on 100% renewable energy systems finding that there is consensus in the scientific community that 100% renewable energy systems are indeed technically and economically feasible. One thing that was also identified in the study is a lack of studies on the Global South.…”
Section: Energy Transition In the Global Southmentioning
confidence: 99%